Chordicoccus furentiruminis, gen. nov., sp. nov., a novel succinic acid producing bacterium isolated from a steer on a high grain diet. Issue 3 (1st March 2023) - Gaffney, James; Embree, Jordan; Gilmore, Sean; Embree, Mallory
Abstract : This study presents MP1D12 T (=NRRL B-67553 T =NCTC 14480 T ), an isolate from the ruminal content of an Angus steer fed a high grain diet. Phenotypic and genotypic traits of the isolate were explored. MP1D12 T was found to be a strictly anaerobic, catalase-negative, oxidase-negative, coccoid bacterium that frequently grows in chains. Analysis of metabolic products as a result of carbohydrate fermentation showed succinic acid as the major organic acid produced with lactic acid and acetic acid as minor products. Phylogenetic analysis of MP1D12 T based on 16S rRNA nucleotide sequence and amino acid sequences from the whole genome presents a divergent lineage from other members in the family Lachnospiraceae . 16S rRNA sequence comparison, whole genome average nucleotide identity digital DNA–DNA hybridization and average amino acid identity results suggest that MP1D12 T represents a novel species in a novel genus within the family Lachnospiraceae . We propose the creation of the genus Chordicoccus in which MP1D12 T represents the type strain for the novel species Chordicoccus furentiruminis .